Design of position control of a DC motor with simplified hardware - Butler Blacker, Jorge Gustavo (2009)
In this work is presented the required details for the design a DC motor positioning control, having into account the parameters of the motor given by the manufacturer. It is explain in detail the method used to find their operation parameters, with the controller parameter, the Kalman and control constants are calculated. All of those used in the C++ language as well as in DSP assembler. With the data collected in real time is produced the control signal that also is obtained from C++, finally we drew the results in DSP assembly language.